To remit, or not to remit: That is the question. A remittance field experiment - Torero, Máximo; Viceisza, Angelino (Elsevier, 2015)
We conduct a remittance field experiment among Salvadoran migrants in the metro DC area. Migrants need to decide whether or not to remit funds to a recipient in El Salvador and if so how much. We maintain a (2 × 2) design in which the remittance budget has a value of $400 or $200, and the remitted funds arrive as cash or grocery vouchers that are non-transferable and applicable to basic necessities that do not include alcohol and cigarettes. Each migrant is randomly allocated to one of the resulting four treatments. We test across these treatments whether control over remittance spending in the form of grocery vouchers affects remittance behavior. We find the following. Our quantitative findings suggest that migrants prefer a remittance to arrive as cash than as groceries when stakes are high. This result is robust to inclusion of a wide set of covariates and is consistent with a conceptual framework in which migrants have preferences over how recipients spend remittances. Our qualitative findings suggest that migrants integrate amounts sent in the experiment with the external environment for sending remittances. We explore the mechanisms underlying the main effect and find that migrants who more recently sent a remittance and, in certain specifications, male migrants exhibit a greater preference for cash. Some implications of our findings are discussed.